Motivation beliefs, emotions, leisure time physical activity, and sedentary behavior in university students: A full longitudinal model of mediation. (January 2022) - Garn, Alex C.; Simonton, Kelly L.
Abstract: Discrete emotions produce predictable response tendencies, yet there is limited understanding about their potential to mediate relations between motivation beliefs and leisure time physical activity (LTPA) and sedentary behavior. The current study investigates self-reported moderate LTPA, vigorous LTPA, and sedentary behavior as measured by the Global Physical Activity Questionnaire using control – value theory of achievement emotions (CVTAE) with a full longitudinal mediation design. A total of 586 young adults ( M age = 19.44, SD  = 1.43) completed 1485 time-specific reports of LTPA, sedentary behavior, PA enjoyment, LTPA boredom, and control and value beliefs toward PA across three waves of data collection. Structural equation modeling was used to systematically disentangle direct and indirect relations over time. Neither enjoyment nor boredom mediated relations between participants' control and value beliefs and moderate LTPA, vigorous LTPA, or sedentary behavior; however, boredom did negatively predict vigorous LTPA. There were reciprocal relations between control beliefs and moderate LTPA as well as value beliefs and PA enjoyment. The final model did not support relationships posited by CVTAE for LTPA or sedentary behavior. However, theoretically grounded CVTAE constructs explained substantive amounts of variance in moderate and vigorous LTPA but not sedentary behavior. Highlights: Motivational beliefs predict changes in physical activity enjoyment. Control beliefs are key to changes in moderate and vigorous physical activity. Feelings of boredom reduced future vigorous physical activity. Sedentary behaviors were not related to physical activity beliefs or emotions.